2017
DOI: 10.1093/schbul/sbx048
|View full text |Cite
|
Sign up to set email alerts
|

Altered White Matter Connectivity Within and Between Networks in Antipsychotic-Naive First-Episode Schizophrenia

Abstract: Analyzing the schizophrenia connectome can identify illness-related alterations in connectivity across the brain. An important question that remains unanswered is whether connectivity alterations are already evident at the onset of illness, before treatment with antipsychotic medication and possible influences of neuroprogressive or secondary alterations related to chronic illness duration. In the present study, diffusion tensor imaging and deterministic fiber tractography were performed with 137 antipsychotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 51 publications
2
22
0
1
Order By: Relevance
“…White-matter alterations that occur in the early stages of psychosis may parallel the course of the illness and differentiate the clinical subtypes 9,10,63 . In this cross-sectional work, we investigated the white-matter connectivity of early-psychosis patients (EPPs) in different clinical stages after the first psychotic episode and in comparison with healthy controls (HCs).…”
Section: Discussionmentioning
confidence: 99%
“…White-matter alterations that occur in the early stages of psychosis may parallel the course of the illness and differentiate the clinical subtypes 9,10,63 . In this cross-sectional work, we investigated the white-matter connectivity of early-psychosis patients (EPPs) in different clinical stages after the first psychotic episode and in comparison with healthy controls (HCs).…”
Section: Discussionmentioning
confidence: 99%
“…g) Participation coefficient:: One might also wish to measure how the connections emanating from a node are spread among nodes in the different communities, a notion that is formalized in the participation coefficient [103]: Pi=1k=1Kfalse(SiCkSifalse)2,where S iC k is the strength of edges of node i to nodes in community C k . This statistic has been used to better understand how learning is impacted by patterns of intermodular connectivity [193], how brain function is altered in antipsychotic-naive first-episode schizophrenia patients [131], and how structural modular segregation mediates the relationship between age and executive function in youth [24].…”
Section: Summarizing Community Structure In Brain Graphsmentioning
confidence: 99%
“…Research on subclinical negative symptoms is limited, let alone in association with DWI network alterations. Two studies in individuals at high-risk for psychosis reported a negative association between subclinical negative symptoms and rich-club organization (Schmidt et al 2017;Li et al 2018), while another study reported no associations between network connectivity and subclinical negative symptoms (Zhao et al 2017). In psychotic disorder, absence of an association between negative symptoms and network-based measures (Levitt et al 2017), as well as a negative association between network connectivity and negative symptoms has been described (Qifeng Wang et al 2012a).…”
Section: Associations Between Symptoms and Network Measures In Indivimentioning
confidence: 99%
“…Additionally, decreased local efficiency (defined as how well information circulates over the network (Latora and Marchiori 2003)) has been described in frontal, temporal, (para)-limbic and putamen regions (Q. F. Wang et al 2012b;Yan et al 2015). Findings on the clustering coefficient (CC; measure of local cohesiveness/interconnectedness) are inconsistent, showing increased (Zhang et al 2012), decreased (Li et al 2018) and unchanged CC (Yeo et al 2016). Furthermore, studies have reported negative associations between structural network efficiency on the one hand, and negative and positive symptoms in patients with psychotic disorder on the other (Skudlarski et al 2010;Qifeng Wang et al 2012a).…”
Section: Introductionmentioning
confidence: 99%